PENERAPAN PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN DI KELAS VII SMP - Jessi Claudia Boe (Program Studi PGSD Universitas Flores, 2023)
This study aims to find out how the application of problem-based learning in improving student learning outcomes in class VII Civics learning at SMP Negeri 1 Maumere. This type of research is classroom action research (CAR) with the method used, namely the problem based learning method. This study consisted of two cycles, which consisted of 4 stages, namely: planning, implementing, observing, and reflecting. The subjects of this study were all 32 students in class VII C, while the researcher acted as a teacher. Data collection techniques in this study are tests, observation, and documentation. Data analysis was carried out by comparing the test results in Cycle I and Cycle II with descriptive instructions. This means that the data obtained is presented as is and then analyzed descriptively to get the results. Meanwhile, to measure student learning outcomes using the class average value in each cycle. The results showed that the learning outcomes and learning activities of class VII students of SMP Negeri 1 Maumere in Civics learning had increased, this was shown from: 1) based on the results of observations of students' learning activities, information was obtained that there was an increase from Cycle I to Cycle II both in type visual, verbal, listening, emotional, and mental activities. 2) the increase in class average scores from Cycle I to Cycle II increased by 8.75%, namely from 65 to 75.4. In Cycle II the very high score category of students increased by 12.5% which in Cycle I no students got very high scores but in Cycle II it increased to 4 children in the very high score category. From the results of the study it can be concluded that the problem based learning (PBL) learning method can improve student learning outcomes in class VII Civics learning at SMP Negeri 1 Maumere.